Concentrations of Tetrabromobisphenol-A and hexabromocyclododecane in Thai child daycare centre dust and the exposure risk for young children - Waiyarat S. (2023)
Children spend one-third of their day in child daycare centres, where they may be exposed to toxic chemicals, such as tetrabromobisphenol-A (TBBPA) and hexabromocyclododecane (HBCDD), from indoor dust. However, studies on the exposure of TBBPA and HBCDD in schools remain scarce, especially in Thailand, where no such study has yet been reported. Therefore, in this study, we collected dust samples from 20 child daycare centres in Thailand and analysed them for flame retardants, TBBPA and HBCDD. TBBPA was detected in all samples with a median concentration of 35 ng g−1 (range, 14–5017.7 ng g−1). The median level of HBCDD was lower than the quantitation limit (LOQ) with <LOQ to 86.6 ng g−1 of dust sample. The electronic density score was calculated from the number of electronic appliances divided by each sampled surface floor area that revealed an abundance of TBBPA in the dust in rooms with many electronic items. The use of electronic devices, especially printers, that were found to be related to the high TBBPA concentration in the room, should be minimised in child daycare centres. The children's exposure to these chemicals from dust was estimated for dust ingestion and dermal absorption. The combined exposure was lower than the established reference dose value, and the hazard quotient for children via these two pathways were ranged 0.7 × 10−6 – 2.7 × 10−4 for TBBPA and 1.8 × 10−5 – 4.9 × 10−5 for HBCDD, which did not exceed 1.0. Although there is uncertainty regarding the potential health effects of long-term exposure to these substances, it is undeniable that child daycare centres represent a source of exposure to these substances for children. Further investigation of other intake routes of several flame retardants in child daycare centres and identification of the sources of these substances is warranted to decrease children's health risks from exposure to these harmful substances in child daycare centres.